PENGARUH GAYA KEPEMIMPINAN PARTISIPATIF DAN BUDAYA ORGANISASI TERHADAP PRODUKTIVITAS KERJA PADA PT. MAHA KARYA TEKNOLOGI - Jihan Muthia Rahmah; Dede Andi (Journal of Research and Publication Innovation, 2025)
The purpose of this study is to determine the influence of leadership style and organizational culture on work productivity at PT. Maha Karya Teknologi in West Jakarta, both partially and simultaneously. The method used is quantitative. The sampling technique used Slovin's formula, resulting in a sample of 77 employees for this study. Data analysis included validity tests, reliability tests, classical assumption tests, multiple regression analysis, coefficient of determination analysis, and hypothesis testing. The analysis results showed that the simple regression equation is Y = 10.551 + 0.235X1, and based on the t-test between the leadership style variable and work productivity, the t-value is 1.579 > 0.66769 (t-table), indicating that leadership style influences work productivity. The results also showed that the simple regression equation is Y = 10.551 + 0.483X2, and based on the t-test between organizational culture and work productivity, the t-value is 3.722 > 0.66769 (t-table), indicating that organizational culture influences work productivity. The analysis further revealed that the multiple regression equation is Y = 10.551 + 0.235X1 + 0.483X2, and the Adjusted R Square value is 0.801, meaning that 80.1% of the variation in work productivity is explained by the influence of leadership style and organizational culture simultaneously, while the remaining 19.9% is influenced by other variables.